2021
DOI: 10.3390/ijerph18137030
|View full text |Cite
|
Sign up to set email alerts
|

Functioning and Cognition of Portuguese Older Adults Attending in Residential Homes and Day Centers: A Comparative Study

Abstract: The functioning and cognition of older adults can be influenced by different care contexts. We aimed to compare the functioning profiles and cognition of institutionalized and noninstitutionalized older adults and to evaluate the effect of sociodemographic factors on the functioning and cognition. This is a cross-sectional study that included 593 older adults. The data were collected using the Elderly Nursing Core Set and Mini Mental State Examination. Women, older adults who did not attend school and those li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…We found studies that confirm these results, assuming there are no great differences between the sexes in ages above 65 years and concluding that sex is not a major predictor of dependence levels ( James et al, 2018 ; Ek et al, 2021 ). On the other hand, we have also found evidence from other authors concluding that females experience higher levels of functional dependence ( Schmitz and Lazarevič, 2020 ; Fonseca et al, 2021 ; Lopes et al, 2021 ). It is necessary to take into account the fact that females live longer, so reaching more advanced stages of life gives them a degree of dependence that men do not tend to reach because they die earlier, which is a phenomenon referred to as the “feminization of old age” ( Goes et al, 2020 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found studies that confirm these results, assuming there are no great differences between the sexes in ages above 65 years and concluding that sex is not a major predictor of dependence levels ( James et al, 2018 ; Ek et al, 2021 ). On the other hand, we have also found evidence from other authors concluding that females experience higher levels of functional dependence ( Schmitz and Lazarevič, 2020 ; Fonseca et al, 2021 ; Lopes et al, 2021 ). It is necessary to take into account the fact that females live longer, so reaching more advanced stages of life gives them a degree of dependence that men do not tend to reach because they die earlier, which is a phenomenon referred to as the “feminization of old age” ( Goes et al, 2020 ).…”
Section: Discussionsupporting
confidence: 87%
“…There are several recent studies that corroborate these results, indicating that lower levels of education are associated with higher levels of dependence ( Serrano-Alarcón and Perelman, 2017 ; Abalo et al, 2018 ; Coutinho et al, 2018 ; Cui et al, 2019 ). In addition, a Portuguese study that evaluated the functional and cognitive profiles of both the institutionalized and noninstitutionalized older population, as well as the consequence of sociodemographic factors on functionality and cognition, concluded that the lack of education is one of the main predictors of decreased functionality at elderly ages ( Lopes et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As of 1960, life expectancy in Ghana was 46.9 years, however, in 2020, it increased to 63.7 years which is further projected to increase to 70 years by 2050, and 76.2 years by 2100 (Awuviry-Newton et al ., 2021; UN, 2019). Meanwhile, this increase in life expectancy is not tantamount to an increase in good health (Lopes et al ., 2021). This is a clear-cut indication of the impending burden of care for the aged.…”
Section: Introductionmentioning
confidence: 99%
“…Functionality is an important component in the QoL of older people, as its decline implies a loss of autonomy [ 3 ]. Poor functionality impairs the performance of basic activities of daily living (ADL), which include adequate preparation and consumption of food and activities that promote physical and mental well-being [ 4 ].…”
Section: Introductionmentioning
confidence: 99%